256 Physical exercise during working hours for employees at a hospital laundry – a qualitative process evaluation. (24th April 2018) - Panduro, MB; Andersen, LL; Brandt, L
Abstract : Introduction: The present study is to provide an understanding of the motivational factors and barriers that influence compliance with physical exercise during working hours that are aimed at reducing musculoskeletal disorders, for employees at a hospital laundry. Methods: This study used a semideductive, thematic, and structured in-depth interview that was nested in an ongoing project with 140 laundry employees at a hospital laundry with 3 different geographic locations, that have been physical active at work since January 2015. The interviews was conducted 72 weeks within the main project among 22 informants with diverse field of laundry work, where the majority participated in the resistance band training at the workplace for 5 min, three times per week. The following factors, organisational, implementational, and individual motives and barriers were explored. Result: The results indicates that there should be attention to the interaction between management, the employees and the aim of the intervention, since the main barrier for compliance in this study is internal working culture. The results emphasised a certain need of clear connexion between the management's intentions of the implementation of physical exercise at work and the actual implementation. There was also a strong correlation between the employee's motivation and participation in relation to the manager's participation at the daily physical exercise at the workplace. Additionally the results emphasise the importance of ensuring the cooperation among manager's, participants and colleagues in order to ensure compliance regarding the intervention. Discussion: Our recommendations from this study suggest a thorough pre-evaluation in order to analyse the organisational and implementation factors before the implementation of physical exercise at work.